Learning Chinese characters: a comparative study of the learning strategies of western students and Eastern Asian students in Taiwan - Hsu, Jui Fang, author; Flahive, Doug, advisor; Fabiola, Ehlers-Zavala, committee member; Fan, Chuen-mei, committee member (Colorado State University. Libraries, 2012)
Vocabulary acquisition is central to learning Chinese as second or foreign language. Little research has been conducted on vocabulary learning strategies in this area. Even less study has been conducted whether students from different native language background would apply vocabulary learning strategies differently. The present study was designed to address this gap. The major concern of this study was to explore whether students from Western alphabetic countries and students from Eastern Asian countries would apply different vocabulary learning strategies in Chinese vocabulary acquisition. All the participants are international students who currently reside in Taiwan and attending the same American School located in Taipei, Taiwan. Learning Chinese is mandatory in the school. An on line survey instrument was used to collect data from the students. Descriptive statistics were used. An independent samples t-test was used to assess whether students of different native language background showed significant differences in the application of vocabulary learning strategies. No significant difference was found, however, suggestions regarding curricula design in learning Chinese vocabularies were made based on the tentative findings of this study.